FRI0332 Normalization of Serum Uric Acid Levels After Allogeneic Hematologic Stem Cell Transplantation. (9th June 2015) - Joo, S.H.; Song, Y.W.; Yoon, S.-S.; Park, J.K.
Abstract : Background: Cell turnover in the hematopoietic system constitutes a major site of purine salvage and metabolism. Pathologically accelerated cell turnover with hematologic malignancies increases the delivery of purines to the liver, and hepatic xanthine oxidase metabolizes them into uric acid (UA), resulting in increased serum UA levels. The long-term effects of hematopoietic stem cell transplantation (HSCT) on serum UA levels have not been characterized. Objectives: To define whether restoration of bone marrow function after HSCT is associated with normalization of serum UA levels Methods: In this retrospective study, serum UA levels of 93 patients who underwent HSCT at our institution between 2001 and 2012 were analyzed. All patients received allopurinol 300 mg daily for 7 days as a prophylaxis of tumor-lysis syndrome during myeloablative conditioning. Serum UA levels were analyzed at days 90±14 and 8 before HSCT, on the day of transplantation, and at days 90±14 and 365±14 after HSCT. Results: At baseline, the mean UA level was 4.9±2.1 mg/dL; the prevalence of hyperuricemia was 18% (defined as serum UA >6.8 mg/dL). UA levels dropped significantly with myeloablative conditioning and concomitant allopurinol, reaching a nadir on the day of HSCT. In the 3 months following transplantation, UA levels rose sharply and remained stable up to 1 year after HSCT (Figure 1A ). Patients were grouped into quartiles according to their baseline UA levels and changes of each quartile were monitored over time. UA levels in the different quartiles seemed to converge with time (Figure 1B ). In addition, recipient UA levels at 12 months after HSCT correlated with those of their respective graft donors (Pearson r =0.317, p=0.011). Conclusions: Restoration of normal hematopoietic function after HSCT is associated with long-term normalization of uric acid levels. References: Cannell PK, Herrmann RP. Urate metabolism during bone marrow transplantation. Bone Marrow Transplant. 1992;10(4):337-9. Disclosure of Interest: None declared